ANALISIS KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN Z-SCORE, SPRINGATE, ZMIJWESKI, FOSTER, DAN GROVER PADA BANK MANDIRI Tbk. - Saputra, Irfan; Chandra Hermanto, Willi; Azmi, Zul; Akhmad, Ikhbal (Research in Accounting Journal (RAJ), 2021)
This research is motivated by the passion to provide an overview of the bankruptcy method, in terms of bankruptcy analysis. The writing of this article aims to provide a comprehensive view and description of the bankruptcy analysis method which is classified into several methods including: Altman Z-Score, Springate, Zmijweski, Foster, and Grover methods. The results of this study are expected to be used by readers in making financial decisions related to Bank Mandiri Tbk. For academics, this paper is useful for adding insight and bringing theoretical concepts closer to a practical level. Based on the discussion in this study, basically the existing analysis method is not merely an absolute consideration in making decisions but aims to be a complement or activity that has a measuring value that can add understanding and truth to reality with existing financial reporting.